2018
DOI: 10.21468/scipostphys.4.2.010
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure of the candidate 2D Dirac semimetal SrMnSb2: a combined experimental and theoretical study

Abstract: SrMnSb 2 is suggested to be a magnetic topological semimetal. It contains square, 2D Sb planes with non-symmorphic crystal symmetries that could protect band crossings, offering the possibility of a quasi-2D, robust Dirac semi-metal in the form of a stable, bulk (3D) crystal. Here, we report a combined and comprehensive experimental and theoretical investigation of the electronic structure of SrMnSb 2 , including the first ARPES data on this compound. SrMnSb 2 possesses a small Fermi surface originating from h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 40 publications
8
36
0
Order By: Relevance
“…Such control can potentially be realized in materials in which magnetic order coexists with non-trivial electronic band topology. Recent ARPES, quantum oscillation, neutron diffraction and ab initio band structure studies suggest that materials in the AMnSb 2 (A = Ca, Sr, Ba, Eu, Yb) family display many of the required properties [9][10][11][12][13][14][15][16][17][18] . The two-dimensional zig-zag layer of Sb atoms [ Fig.…”
mentioning
confidence: 99%
“…Such control can potentially be realized in materials in which magnetic order coexists with non-trivial electronic band topology. Recent ARPES, quantum oscillation, neutron diffraction and ab initio band structure studies suggest that materials in the AMnSb 2 (A = Ca, Sr, Ba, Eu, Yb) family display many of the required properties [9][10][11][12][13][14][15][16][17][18] . The two-dimensional zig-zag layer of Sb atoms [ Fig.…”
mentioning
confidence: 99%
“…The nontrivial topological semimetal behavior was further supported by optical conductivity and ultrafast optical pump-probe measurements [4]. Nevertheless, Ramankutty et al [5] reported zero Berry phase indicative of trivial topology in nearly stoichiometric SrMnSb 2 . Previous density functional theory (DFT) calculations [5][6][7] showed that the lattice distortion in the orthorhombic structure prevents the formation of the Dirac points near the Fermi level by opening a gap.…”
mentioning
confidence: 90%
“…Nevertheless, Ramankutty et al [5] reported zero Berry phase indicative of trivial topology in nearly stoichiometric SrMnSb 2 . Previous density functional theory (DFT) calculations [5][6][7] showed that the lattice distortion in the orthorhombic structure prevents the formation of the Dirac points near the Fermi level by opening a gap. Both results cannot account for the observed topological semimetallic behavior reported in Ref.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that, recent ARPES, transport measurements, and density functional theory (DFT) and tight binding calculations show that the electronic bands are gapped above the Fermi energy for SrMnSb 2 , suggesting trivial topology [21]. The extracted Berry phase is zero, indicating the non-topological character of the transport in SrMnSb 2 [21], whereas the non-trivial π Berry phase was observed in Type A crystals in Ref. [20].…”
Section: Introductionmentioning
confidence: 95%